Pembinaan kemahiran berbahasa arab pada santri tpq qurrata a’yun boyolali - Syamsiyah, Barid (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2022)
The purpose of this research is to find out the development of Arabic proficiecy in TPQ Qurrata A’yun Boyolali Students as well as the effects of fostering Arabic proficiency in TPQ Qurrata A’yun Boyolali students. The method used in this research is descriptive qualitative method. Data collection methods through observation, interviews and documentation. Analysis of research data using source data reduction, data presentatio and conclusion. The result showed that the development of arabic language proficiency of the TPQ Qurrata A’yun students was divided into two, namely the development of reading and writing skills using the game method and arabic songs. The game method includes playing in bold letters, connecting letters and composing verses. While the song method is the translation of the names of the letters in juz 30. The positive impact of fostering Arabic proficiency is that students are able to read Iqra’ and the Koran with good and correct rules, students are able to translate some of the names of letters in juz amma, namely letters an-nas to letters ad-dhuha, students are able to write the names of letters in Arabic, student are increasingly enthusiastic about learning arabic through learning the Qur’an. Keywords: Coaching, Reading Skills, Writing Skills, TPQ